2011
DOI: 10.1007/s10902-011-9262-x
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Happiness in Children in India

Abstract: The relation between temperament and happiness was assessed in a sample of 441 children aged 7-14 years drawn from a population in Northern India. Parents assessed their children's happiness and rated their children's temperament using the Emotionality, Activity, and Sociability Temperament Survey (EAS). Children self-reported their own happiness using a single-item measure, the Oxford Happiness Scale Short Form, and the Subjective Happiness Scale. Parents' temperament ratings conformed to the four factor stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 67 publications
3
23
0
1
Order By: Relevance
“…Despite the emergence of positive psychology, there are few studies on children's and adolescents' happiness, only having begun in the 1990s (Chaplin, 2009). This is extremely surprising, given that happiness is one of the first emotions recognized by children (e.g., Harter, 1983;Pollack & Sinha, 2002) and that it entails positive benefits for children's and adolescents' well-being (e.g., Holder, Coleman, & Singh, 2012).…”
Section: Parent-child Discrepancies In the Assessment Of Children's Amentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the emergence of positive psychology, there are few studies on children's and adolescents' happiness, only having begun in the 1990s (Chaplin, 2009). This is extremely surprising, given that happiness is one of the first emotions recognized by children (e.g., Harter, 1983;Pollack & Sinha, 2002) and that it entails positive benefits for children's and adolescents' well-being (e.g., Holder, Coleman, & Singh, 2012).…”
Section: Parent-child Discrepancies In the Assessment Of Children's Amentioning
confidence: 99%
“…However, there is little agreement on the assessment of happiness, leading researchers to use multiple measures (e.g., Holder et al, 2012) to better capture the distinct facets that cover this construct. For both adults and children, multiple single item measures, such as the Faces Scale (Holder et al, 2012) are regularly used, as they have been shown to be valid and reliable (Abdel-Khalek, 2006).…”
Section: Parent-child Discrepancies In the Assessment Of Children's Amentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing primarily on the positive emotions component of Diener's (1984) definition of subjective well-being, Holder et al (2012) investigated the happiness of children and young adolescents in India. A sample of 441 youth ages 7-14 years reported their levels of happiness, and their parents also reported their observations of their children's happiness.…”
Section: Introductionmentioning
confidence: 99%
“…For instance Mark and Holder assessed the correlation between temperament and happiness in 311 children aged 9 to 12 years old and showed that being physically and socially active, less shy, and excited are mentioned as indices that increase happiness among participants (29), which is in accordance with PM perspectives. In the viewpoint of PM, high physical and social mobility and energy indicate warmness of Mizaj (7).…”
Section: Discussionmentioning
confidence: 70%